Emergent leadership: a comprehensive analysis of stages and relevance in performance sports - Mateescu, A. D.; Marci, A. C.; Amzar, E. L.; Larisa, R. (Journal of Physical Education and Sport, 2024)
This article presents a thorough examination of the process of selecting a team captain through emergent leadership, focusing on various aspects and implications. The objective of this study was to clarify the 'Process of selecting the team captain through emergent leadership' by examining each stage of this process. Over a year, we conducted semi-structured qualitative interviews with 25 athletes and coaches (12 males and 13 females). The investigation revealed a detailed 'Team captain identification process,' outlined through five primary themes, highlighting the complex interaction between the roles, attributes, selection, tenure, and conclusion of a team leader's term. Notably, the findings underscore the multifaceted nature of leadership in sports teams,underscoring the significance of non-playing responsibilities, personality traits, and athletic performance in the captaincy role. Furthermore, the study emphasises the crucial role of coaches in facilitating the selection and development of team captains, advocating for a comprehensive approach that fosters leadership qualities among all team members. By providing deeper insights into the dynamics of captaincy selection, this research contributes valuable insights to sports management and leadership literature. It underscores the importance of thoughtful consideration and continuous assessment in choosing captains capable of effectively leading, motivating, and unifying their teams, thereby enhancing overall team cohesion and performance. Ultimately, the 'Selection process of the team captain through spontaneous leadership' emerged as a dynamic framework to aid leaders in identifying individuals who embody their team's values and aspirations, fostering sustained success on and off the field.